Overview of energy management for smart buildings: an opportunity for engineers in Peru - Delgado Cusi, Rossler Kinverlin (2022)
This article is important for professionals related to the world of infrastructure and building, because it provides what is necessary to understand energy management in buildings. It is also important for the technological impact it provides to users [22]. This research analyzes the energy management in smart buildings in Peru through methodologies such as the review of articles published in the Scopus database using the VOSviewer software as a data analysis tool. This analysis has a period from the XXI century to the year 2021. Graphs related to the research of the database were obtained where the words "intelligent building" and "energy management" are highlighted with greater congruence and mentioned in these journals. Figures were obtained worldwide and in Peru. The results allowed us to understand that smart buildings are becoming more important in developed countries and opening new markets since there are unmet needs of users. In the analysis of Peru, the opposite happens since there are minimal scientific contributions related to the subject. They still do not have intelligent buildings 100% but there are some buildings where energy management is carried out in minimum proportion. An energy management software related to big data called smart building was also found, which has the objective of managing energy consumption in each building to reduce the carbon footprint emitted by buildings. This research is intended to guide you to start with in-depth research and implementation projects for engineers and architects interested in developing and managing intelligent edifications. Nowadays, the importance of studying this topic is to take care of the environment as social and professional responsibility. For this reason, the professionals should opt for better strategies for energy management thus positively impact Peru.